PASAL PENCEMARAN NAMA BAIK DALAM PERPEKTIF HUKUM POSITIF - JUSNIZAR SINAGA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Through various types of social media, everyone can experience the benefits of information technology, namely through the social networks Facebook, Twitter, Instagram, and so on without having to meet face to face. The awareness of some people to write and express opinions wisely through social media sometimes does not maintain behavior and ethics in interacting so that it is considered to cause problems as a result of what they upload, clash with the respect of others, one of which is the problem of defamation through social media with the existence of norms regulate it, but in proving the existence of an insult or defamation and the element of the offense is subjective in nature, it is different from the formulation of other offenses which are always formulated more objectively such as theft offenses. Called offense is subjective because it can only be assessed by the person concerned or the target target called the victim. It cannot be denied that the article regarding defamation in the Constitution of electronic information and transaction can be considered a “rubber article” apart from the fact that the offense element is subjective as well because there are no clear parameters and many acts can be classified as defamation. Then the article has the potential to be misused, thus threatening freedom of expression.